Hysterectomy and Adnexal Procedures by Vaginal Natural Orifice Transluminal Endoscopic Surgery (VNH): Initial Findings From a Korean Surgeon - Kim, Myeong-Seon; Noh, Joseph J.; Kim, Tae-Joong (Frontiers in Medicine, 2021)
Objective: To evaluate feasibility and safety of hysterectomy and adnexal procedures by vaginal natural orifice transluminal endoscopic surgery (vNOTES) Study Design: This is a prospective observational study at a tertiary center and teaching university hospital. We enrolled prospectively 34 patients with benign diseases sequentially. Results: We measured baseline characteristics, surgical data, and pain score (VAS) after surgery. We surveyed before/after surgery. The time of port installation and each stage of surgery was measured. The learning curve was assessed through the graph according to the number of operations using linear and logarithmic regression curve estimation. The complications of surgery were investigated. The median age of the patients was 47.5 years (38-73). Median BMI was 22.4 (18.2-30.0). 20 cases of leiomyoma, four cases of adenomyosis, three cases of uterine prolapse, four cases of endometrial hyperplasia, and three cases of CIN were diagnosed. The median uterine weight was 180.0 g. The median port-installation time was 15.0 min (range, 4–35 min) and median total operation time was 85.5 min (range 43.0–132.0). Complications occurred in three patients. Two cases of bladder injury happened during vesicovaginal space dissection before the installation of the Wound Retractor (WR). One patient underwent transumbilical single-port surgery because of late-onset postoperative bleeding on the thirteenth postoperative day. The mean postoperative VAS scores were 3.36 immediately after surgery and 3.06, 2.79, and 2.45 at 6, 12, and 24 h after surgery, respectively. In continuous variable analysis, we detected a correlation between port-installation time and postoperative VAS ≥ 4 (pain score as need for medication). Based on a learning curve, port-installation time and total operation time appeared to reach the proficiency level by the tenth case. Conclusions: Although there were three complications, vNOTES offers advantages to patients and surgeons. More surgical techniques will be developed in vNOTES.